Little Divergence Among Mitochondrial Lineages of Prochilodus (Teleostei, Characiformes) - Melo, Bruno F.; Dorini, Beatriz F.; Foresti, Fausto; Oliveira, Claudio (Frontiers in Genetics, 2018)
Evidence that migration prevents population structure among Neotropical characiform fishes has been reported recently but the effects upon species diversification remain unclear. Migratory species of Prochilodus have complex species boundaries and intrincate taxonomy representing a good model to address such questions. Here, we analyzed 147 specimens through barcode sequences covering all species of Prochilodus across a broad geographic area of South America. Species delimitation and population genetic methods revealed very little genetic divergence among mitochondrial lineages suggesting that extensive gene flow resulted likely from the highly migratory behavior, natural hybridization or recent radiation prevent accumulation of genetic disparity among lineages. Our results clearly delimit eight genetic lineages in which four of them contain a single species and four contain more than one morphologically problematic taxon including a trans-Andean species pair and species of the P. nigricans group. Information about biogeographic distribution of haplotypes presented here might contribute to further research on the population genetics and taxonomy of Prochilodus.